Depiction of gender in ELT textbooks: gender stereotyping in language and its effect on secondary level students - Hossain, Anika Tasnim (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.